(untitled) - Spranger, Jürgen W.; Jürgen W. Spranger; Paula W. Brill; Andrew K. Poznanski (Oxford,New York, 2002)
This book is designed for physicians involved in the evaluation and treatment of patients with skeletal dysplasias, including radiologists, medical geneticists, pediatricians, and orthopedic surgeons. Its main goal is to assist in the diagnosis of specific conditions and the care of affected individuals. Though mutations of specific genes can produce dysplasias with very different phenotypes and prognoses, the primarily clinical aim of this book dictated a phenotypic classification in general, with compromises on etiologic grounds where necessary. Since the attempt to diagnose a skeletal dysplasia from single signs, alone or in cominations, is fraught with errors, the authors focus on basic patterns of skeletal abnormalities
Includes bibliographical references and index
Keywords: Diagnosis; Differential; Bones; Bone Diseases; Developmental